ICAR ATRP-induced surface self-assembly in the fabrication of the surface nanostructures. (August 2022) - Wang, Chen; Deng, Haoran; Zhao, Hanying
Abstract: Polymerization induced surface self-assembly (PISSA) technology is a state-of-the-art method in the fabrication of the hierarchical surface nanostructures. Previously, we demonstrated that reversible addition−fragmentation chain transfer (RAFT) polymerization-based PISSA could be used to construct hierarchical surface nanostructures on the silica particles. Atom transfer radical polymerization (ATRP) has many advantages, especially in the synthesis of the macroinitiator. In this research initiators for continuous activator regeneration (ICAR) ATRP-induced PISSA approach is used to fabricate surface nanostructures. Poly(ethylene glycol) (PEG) macroinitiator and poly(oligo(ethylene glycol) monomethyl ether methacrylate- co -2-(2-bromoisobutyrnyloxy) ethyl methacrylate) (P(OEGMA- co -BIEM)) polymer brush macroinitiator on silica particles are used to initiate ATRP of styrene in methanol/water mixture. With the chain extensions, POEGMA- g -PS graft copolymer brushes and "free" PEG- b -PS block copolymer chains make surface coassembly into surface nanostructures. With an increase in monomer feeding ratio, the surface morphology gradually changes from small-sized spherical surface micelles (s-micelles), to big-sized s-micelles, and to asymmetric layered structures. Kinetics studies indicate that with an increase in monomer conversion there is a transition from homogeneous to heterogeneous polymerization. Graphical abstract: Image, graphical abstract